Just like that - Schmidt, Gary D. (Clarion Books, Houghton Mifflin Harcourt, 2021)
With insight and a light touch, best-selling, Newbery Honor-winning author Gary D. Schmidt tells two poignant, linked stories: that of a grieving girl and a boy trying to escape his violent past. Following the death of her closest friend in summer 1968, Meryl Lee Kowalski goes off to St. Elene's Preparatory Academy for Girls, where she struggles to navigate the venerable boarding school's traditions and a social structure heavily weighted toward students from wealthy backgrounds. In a parallel story, Matt Coffin has wound up on the Maine coast near St. Elene's with a pillowcase full of money lifted from the leader of a criminal gang, fearing the gang's relentless, destructive pursuit. Both young people gradually dispel their loneliness, finding a way to be hopeful and also finding each other.